Perhitungan Harga Pokok Produksi Menggunakan Metode Job Order Costing Untuk Menentukan Harga Jual Dan Meningkatkan Akurasi Laba/Rugi (Studi Kasus Pada Konveksi “Hangar Merch Army”) - Rizky Amalia; Arie Apriadi Nugraha (Indonesian Accounting Literacy Journal, 2023)
Hangar Merch Army is a business engaged in convection or clothing production. In the process of calculating production costs, the company has not calculated the cost of goods produced appropriately. The company only charges direct raw material costs, direct labor costs and not all of the factory overhead costs that have an impact on the actual selling price and profit and loss. The purpose of this study is to determine the calculation of the cost of goods produced using the job order costing method in the case study of an order for 155 units of BDU Malvinas Scuba. The research method used is descriptive method. The data collection techniques used in this research are interviews and documentation. Based on the results of the study, it is known that the calculation of the company's cost of goods amounted to Rp14,233,030 or Rp91,826/unit with a selling price of Rp120,000/unit. Meanwhile, the calculation of the cost of production using the job order costing method is Rp14,801,270 or Rp95,492/unit with a selling price of Rp125,000/unit. The calculation of the cost of production and selling prices using the job order costing method is higher than according to the company so that in the income statement, the profit earned is Rp. 206,760 greater than according to the company.